Examination of burden of skeletal-related events in patients naive to denosumab and intravenous bisphosphonate therapy in bone metastases from solid tumors population. (4th March 2019) - Bhowmik, Debajyoti; Song, Xue; Intorcia, Michele; Gray, Stephani; Shi, Nianwen
Abstract: Objectives: Skeletal-related events (SREs), i.e. pathologic fractures, spinal cord compression, surgery and radiation to bone, are serious skeletal complications that occur frequently in patients with bone metastases (BMs) from solid tumors (STs). Clinical guidelines recommend treatment with denosumab and intravenous bisphosphonates (IVBPs) to prevent SREs. However, therapy may be delayed by physicians due to perceived low risk of SREs or for other clinical reasons. This study estimated SRE incidence rates in treatment-naive (i.e. no denosumab or IVBPs) patients with BMs from STs in the US. Methods: In this retrospective cohort study adult patients with diagnoses of BM and ST between 1 January 2008 and 31 March 2015 were identified from MarketScan Databases. All patients had ≥6 months of data before the first BM diagnosis date (index date) and were followed for ≥6 months from the index date until the earliest of inpatient death, initiation of denosumab/IVBP therapy or end of data. The Kaplan–Meier curve was used to estimate cumulative incidence of SREs. The incremental healthcare cost of SREs was estimated and compared to propensity score matched non-SRE patients. Results: A total of 47, 052 patients met the study criteria. Using the Kaplan–Meier method the cumulative incidences of SREs among treatment-naïve patients were 39.9% (95% confidence internal [CI]: 39.4–40.4), 46.3% (95% CI: 45.8–46.8), 52.5% (95% CI: 51.9–53.2) and 59.4% (95% CI: 58.6–60.3) by month 6, 12, 24 and 48 post index date, respectively. The SRE group was associated with higher all-cause total healthcare cost per-patient-per-year compared to those without SREs (168, 277 vs. 101, 020, p < .001). Conclusions: Almost half (46.3%) of the treatment-naïve population with BMs from STs experience SREs within 1 year of the first BM diagnosis. SREs were associated with an average 67, 257 additional healthcare cost annually. Given the high SRE burden in these patients, early initiation of prophylactic therapy should be considered.